2014
DOI: 10.1021/ic501329p
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Superoxide Dismutase (SOD) Mimics: The Evaluation of the Therapeutic Potential of New Cationic Mn Porphyrins with Linear and Cyclic Substituents

Abstract: Our goal herein has been to gain further insight into the parameters which control porphyrin therapeutic potential. Mn porphyrins (MnTnOct-2-PyP5+, MnTnHexOE-2-PyP5+, MnTE-2-PyPhP5+, and MnTPhE-2-PyP5+) that bear the same positive charge and same number of carbon atoms at meso positions of porphyrin core were explored. The carbon atoms of their meso substituents are organized to form either linear or cyclic structures of vastly different redox properties, bulkiness, and lipophilicities. These Mn porphyrins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 127 publications
3
44
0
1
Order By: Relevance
“…The E 1/2 for any couple that involves species in high-oxidation states (eqs [3] and [4]) are similar for all Mn porphyrins (see under Catalysis of H 2 O 2 dismutation by Mn porphyrins); thus the 2 nd step, electron transfer, has no impact on the magnitude of k cat (H 2 O 2 ). In turn, the p K a(ax) was reported and confirmed here with new MnPs [49] to parallel the E 1/2 of Mn III P/Mn II P redox couple (C) [50, 68]. Consequently, the log k cat (H 2 O 2 ) paralells the E 1/2 of Mn III P/Mn II P redox couple (A) though this couple is not involved in H 2 O 2 dismutation.…”
Section: Figuresupporting
confidence: 82%
See 1 more Smart Citation
“…The E 1/2 for any couple that involves species in high-oxidation states (eqs [3] and [4]) are similar for all Mn porphyrins (see under Catalysis of H 2 O 2 dismutation by Mn porphyrins); thus the 2 nd step, electron transfer, has no impact on the magnitude of k cat (H 2 O 2 ). In turn, the p K a(ax) was reported and confirmed here with new MnPs [49] to parallel the E 1/2 of Mn III P/Mn II P redox couple (C) [50, 68]. Consequently, the log k cat (H 2 O 2 ) paralells the E 1/2 of Mn III P/Mn II P redox couple (A) though this couple is not involved in H 2 O 2 dismutation.…”
Section: Figuresupporting
confidence: 82%
“…Same dramatic impact of hydrogen bonding was demonstrated on the metalation rate of H 2 TnBuOE-2-PyP 4+ [47]. With MnTnHexOE-2-PyP 5+ , however, oxygen atoms are buried deeper into the hexoxyethyl chains resulting in lesser impact; in turn the log k cat (H 2 O 2 ) is closer to the value for alkyl analogs, MnTnHex(or Oct)-2-PyP 5+ [49]. The hindrance of the oxygen atoms from the solvent is also reflected in the lipophilicity of MnTnHexOE-2-PyP 5+ which is closer to the one of the alkyl analog of same number of carbon atoms in pyridyl substituents, MnTnNon-2-PyP 5+ .…”
Section: Resultsmentioning
confidence: 94%
“…The ascorbate oxidation was catalyzed by endogenous metalloproteins, presumably metal-containing porphyrins such as cyt P450 family of enzymes [39-41]. We have already indicated that cationic MnPs may be better catalysts for ascorbate oxidation than endogenous metalloproteins [33, 42-45]. Others subsequently confirmed that MnP-driven catalysis of ascorbate oxidation bears anticancer therapeutic potential [39, 46-49].…”
Section: Introductionmentioning
confidence: 99%
“…Its oxidation, catalyzed by endogenous metalloproteins resulting in cytotoxic H 2 O 2 production, was proposed as its mode of action. However, we have shown that cationic Mn(III) ortho N -substituted pyridylporphyrins, one of which will be used herein, are superior to endogenous metalloproteins as they are optimized as catalysts for ascorbate oxidation [30, 40]. Thus, such MnPs are prospective for clinical development as enhancers of ascorbate/H 2 O 2 driven cancer cell killing.…”
Section: Introductionmentioning
confidence: 99%